Looming of Ecological Toxinology - Liu, Zhirui; Zhou, You; De Lima, Maria Elena; Ji, Yonghua (Venoms and Toxins, 2021)
Ecological and environmental management are key factors governing the sustainable development of society. For years, persistent and severe problems have occurred in many aspects that have greatly influenced the environment with the rise of economy and technology worldwide. Although efforts have been made to reduce the pollutants, it remains a substantial problem to be solved due to the lack of knowledge of ecological toxinology. In this review, we will begin with several ecological disasters happened in past decades, originated from toxic pollutants, human activity, venomous species and deadly virus. By exemplifying the long-lasting influence and cause of these biological events, extensive warning and social recognition will hopefully be promoted. Furthermore, from a more academic view, this review will also propose new thinking on some public concerns, such as the unexpected prevalence of severe acute respiratory syndrome (SARS), transgenic food and beyond this. Finally, by combining the ongoing advances in techniques, ways to make a reasonable use of these bio-toxins will be approached, which may help to balance the relationship of environment, human life and economic development.
Keywords: human life